3D dataset from "Methodology to obtain highly resolved SO2 vertical profiles for representation of volcanic emissions in climate models" - Sandvik, Oscar S.; Friberg, Johan; Sporre, Moa K.; Martinsson, Bengt G. (Lund University, 2021)
This dataset has been produced according to the method described in the paper "Methodology to obtain highly resolved SO2 vertical profiles for representation of volcanic emissions in climate models". This is a 3D global dataset of the concentrations of sulfurdioxide in the stratosphere after the volcanic eruption from Sarychev the 11-21 of June 2009.

Data of SO2 concentrations in the stratosphere after the Sarychev 2009 eruption. The data has been put together from the satellite instruments CALIOP and AIRS with the aid of FLEXPART. The data can be used in models as emissions of SO2 from the 2009 Sarychev eruption.

Detta dataset har producerats utifrån metoden beskriven i artikeln "Methodology to obtain highly resolved SO2 vertical profiles for representation of volcanic emissions in climate models". Datat är ett globalt 3D dataset över koncentrationer av svaveldioxid i stratosfären efter vulkanutbrottet från Sarychev den 11-21 juni 2009.

Data över SO2 koncentrationer i stratosfären efter vulkanutbrottet från Sarychev 2009. Datat har tagits fram utifrån data från satellit instrumenten CALIOP och AIRS med hjälp av FLEXPART. Datat kan användas i modeller som utsläpp av SO2 från Sarychev utbrottet.
3D dataset from "Methodology to obtain highly resolved SO2 vertical profiles for representation of volcanic emissions in climate models"
Keywords: Atmospheric conditions; Atmosfäriska förhållanden; SO2 concentrations; SO2 konsentrationer; stratosphere; stratosfär; Climate Science; Klimatvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi